2017
DOI: 10.1016/j.jcorpfin.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Independent director reputation incentives and stock price informativeness

Abstract: We link the reputation incentives of independent directors to the informativeness of stock prices. We show that when more independent directors rank a directorship high, the firm-specific information content in a firm's stock price increases. Further, independent directors with high reputation incentives serve firms that voluntarily disclose more information and display lower crash risk. We find similar results when using plausibly exogenous shocks to the reputation incentives of independent directors. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 77 publications
2
47
0
Order By: Relevance
“…According to the existing research, the corporate governance factors influencing the stock price crash risk mainly include internal factors and external factors. Among them, internal governance factors involve senior management [24], the board of directors [25], major shareholders and institutional investors [26], and internal control information disclosure [13,27], etc., external factors-including securities analysts [28], media [29], religion [30] and institutional environment [31], etc.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…According to the existing research, the corporate governance factors influencing the stock price crash risk mainly include internal factors and external factors. Among them, internal governance factors involve senior management [24], the board of directors [25], major shareholders and institutional investors [26], and internal control information disclosure [13,27], etc., external factors-including securities analysts [28], media [29], religion [30] and institutional environment [31], etc.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…On the one hand, the independent director system requires independent directors to supervise management objectively and independently [46], and curb their bad news hoarding activities. Generally, the higher the proportion of independent directors, the higher the reputation incentives and the greater the supervisory role [25,47]. Academic independent directors mostly come from universities, scientific research institutions and other units.…”
Section: Csr Academic Independent Director and Stock Price Crash Riskmentioning
confidence: 99%
“…In the past decades, researchers have given particular attention to the effect of independent director reputation incentives. For example, Sila et al (2017) find that there is a positive link between independent director reputation incentives and firm transparency [21]. Nevertheless, few studies examine the effect of independent director reputation incentives on CSR.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found some factors that can affect independent directors' ability of protecting stakeholders, such as their social connections [29], their personal characteristics [28,30], their compensations [31], and so on. Given the important of reputation incentives, a growing number of studies have focused on the effect of independent director reputation incentives over the past decades [21]. Yet, no studies have examined how independent director reputation incentives affect CSR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation